Government expenditure and economic growth in ASEAN-5: long -run tendencies and short-term adjustment. - Rajabi, Ehsan; Muhammad, Junaina (IJRCM, 2013)
A question of whether the government should intervene to correct for short-run fluctuations in economic activity has always been an interesting topic for economists. This paper investigates the impact of government expenditure on the economic growth in ASEAN-5 countries during 1980-2006 by using Pooled Mean Group. To examining both short run and long run effects, findings demonstrate that a large government expenditure influences the economic growth of countries negatively. This negative impact may be a sign of the lower productivity of the capital input in ASEAN-5 economies with a large government expenditure.